2011
DOI: 10.3414/me11-06-0002
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis and Data Mining: Current Issues in Biomedical Informatics

Abstract: Summary Background Medicine and biomedical sciences have become data-intensive fields, which, at the same time, enable the application of data-driven approaches and require sophisticated data analysis and data mining methods. Biomedical informatics provides a proper interdisciplinary context to integrate data and knowledge when processing available information, with the aim of giving effective decision-making support in clinics and translational research. Objectives To reflect on different perspectives rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Here we demonstrate that this technique is also useful for single cell migration tracking data. In addition, the data mining approach has been successfully applied to analyzing biological and biomedical data 41–43 . Our results based on the PCA analysis demonstrated that this learning approach is effective in distinguishing the FGF23 pre-treated cells and un-treated control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrate that this technique is also useful for single cell migration tracking data. In addition, the data mining approach has been successfully applied to analyzing biological and biomedical data 41–43 . Our results based on the PCA analysis demonstrated that this learning approach is effective in distinguishing the FGF23 pre-treated cells and un-treated control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ten years ago, visualizing the steps of image processing have been assumed superior to the black box model and making automated computation of images needed to be made transparent to the physicians for trusting them [38,39,40]. Nowadays, since performance evaluation of medical image processing is focused on physicians with vs. physicians without supporting software, rather than physician vs. the software [41], the "black box" model of medical image processing may become in the focus again [42].…”
Section: Resultsmentioning
confidence: 99%
“…While networks and consor- tia are increasing, there are still serious issues that need to be addressed with regard to crossborder exchange of samples and data transfers. 59,60 In addition, informatics challenges in medical biobanking are immense. For instance, there are major challenges associated with the integration of various forms of data such as text (clinical information); numeric values (laboratory data, age); categorical (staging, grading, scoring); image (histology, röntgenology, magnetic resonance); array (genomic data); composite (DNA signatures, mutations, variants, transcription factor interactions); and/or hierarchic (pedigrees) 13,14,15 .…”
Section: 3• Biobanking Challenges In Europementioning
confidence: 99%